THE INTRODUCTION OF INNOVATIVE TECHNOLOGIES IN THE EDUCATIONAL PROCESS OF HIGHER EDUCATION - Abdugalina, S.E.; Baidalina, M.Y.; Iskakova, Z. Zh. (Academic Journal of Physical and Chemical Sciences, 2018)
The most important strategy of the overall national development of Kazakhstan is the modernization of higher education, the purpose of which is to create innovative conditions for students in educational institutions of the country. The transition to a multi-level system of training, improving the competitiveness of educational institutions of higher professional education, the introduction of telecommunications systems and the widespread use of information networks of the Internet allows for a qualitatively new level of training for future specialists ready for innovative technological solutions, creative thinking and tasks in the field of research activities. To improve the quality of the educational process and the effectiveness of the management of the educational process, it is necessary that the organization of informatization covers all the main activities of the institution.